The first report of Hepatozoon sp (Apicomplexa : Hepatozoidae) in neotropical felids from Brazil - Metzger, Betina [UNESP]; Paduan, Karina dos Santos [UNESP]; Rubini, Adriano Stefani [UNESP]; de Oliveira, Tadeu Gomes; Pereira, Cristiane; O'Dwyer, Lucia Helena [UNESP] (Elsevier B.V., 2008)
In order to investigate the occurrence of Hepatozoon infection in Neotropical felids from Brazil, blood from the jugular or cephalic vein was taken from 29 non-domestic felids including ocelot (Leopardus pardalis), little spotted cat (Leopardus tigrinus), margay (Leopardus wiedii), and jaguarondi (Puma yagouaroundi) from the Northeast region of Brazil. Hepatozoon infection was confirmed by light microscopy and molecular techniques. The results showed five naturally infected felids. Partial sequences of the 18S rRNA gene of the Hepatozoon sp. from these felids were further analyzed. Sequences revealed that the isolates found are closely related to Hepatozoon sp. from domestic cats in Spain. Hepatozoon species from Neotropical felids were identified molecularly and characterized for the first time. This is also the first report of Hepatozoon infection in a little spotted cat. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: neotropical felids; Hepatozoon; polymerase chain reaction; molecular characterization; non-domestic cats